1999
DOI: 10.1681/asn.v10122540
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenase-1 Induction Attenuates Inducible Nitric Oxide Synthase Expression and Proteinuria in Glomerulonephritis

Abstract: Abstract. In glomerulonephritis, there is intraglomerular activation of inducible nitric oxide synthase (iNOS) leading to high output production of nitric oxide (NO). This can result in supraphysiologic amounts of NO and cause oxidative injury. It is unknown whether mechanisms of cellular defense against NO-mediated injury exist. Induction of the heme catabolizing enzyme heme oxygenase-1 (HO-1), which generates biliverdin, carbon monoxide (CO), and iron (Fe), may provide such a mechanism, as CO and Fe are two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(9 citation statements)
references
References 38 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…It is important to point out that iNOS and COX-2 are heme-containing proteins the synthesis of which is dependent on the availability of intracellular labile heme. Because the BACH1/HO-1 axis has been shown to regulate intracellular heme levels in LPS-stimulated macrophages [ 49 ], genetic BACH1 deficiency with consequent increase in HO-1 may indirectly impact iNOS and COX-2 expression, as previously reported [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 88%
“…It is important to point out that iNOS and COX-2 are heme-containing proteins the synthesis of which is dependent on the availability of intracellular labile heme. Because the BACH1/HO-1 axis has been shown to regulate intracellular heme levels in LPS-stimulated macrophages [ 49 ], genetic BACH1 deficiency with consequent increase in HO-1 may indirectly impact iNOS and COX-2 expression, as previously reported [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 88%
“…Nrf-2 translocation also regulates the induction of HO-1 [ 46 ]. Previous report also suggests that increased HO-1 expression showed cytoprotective role in cisplatin, rapamycin induced nephrotoxicity, and in ischemia and glycerol induced nephritis [ 47 , 48 ]. This study also showed that HO-1 and HO-2 expression were also down regulated in kidney of ISO administered rats.…”
Section: Discussionmentioning
confidence: 92%
“…Administration of subcutaneous FePP treatment prior to the induction of GN increased glomerular infiltration by HO-1 overexpressing macrophages at early stages (24 h following induction) and reduced proteinuria as well as iNOS expression and activity. It was suggested that HO-1 negatively regulates iNOS in infiltrating macrophages, indicating a switch from a pro- to an anti-inflammatory phenotype [ 82 ]. Interestingly, iNOS-derived NO was a negative regulator of iNOS and also suppressed cyclooxygenase (COX)-2 levels but maintained HO-1 levels [ 76 ].…”
Section: Use Of Mps As Disease Modifying Agents In Renal Immune Injurymentioning
confidence: 99%